Fiscal and monetary stimuli:: Utopia or reality in the Honduran economy in the face of the crisis generated by COVID-19? - Herrera-Herrera, Ana Gabriela (2020)
The current situation has forced countries to confine and consequently stop production, deteriorating productive activity and macroeconomic indicators such as growth in production and employment. Therefore, it is important to analyze whether fiscal and monetary stimulus in economies like Honduras are a reality or a utopia, that is, if they manage to maintain economic stability, so that the productive level is maintained and families do not decrease their income due to unemployment. To carry out the analysis methodologically, a quantitative approach with a descriptive scope was used, which allowed observing that the implemented policies have been insufficient to maintain the economic stability in Honduras because according to projections of the Central Bank of Honduras (BCH) the productive activity will show a growth rate of -8%.